Periods for Calabi--Yau and Landau--Ginzburg Vacua - Berglund, P; Candelas, P; Ossa, X; Font, A; Hubsch, T; Jancic, D; Quevedo, F (1993)
The complete structure of the moduli space of \cys\ and the associated Landau-Ginzburg theories, and hence also of the corresponding low-energy effective theory that results from (2,2) superstring compactification, may be determined in terms of certain holomorphic functions called periods. These periods are shown to be readily calculable for a great many such models. We illustrate this by computing the periods explicitly for a number of classes of \cys. We also point out that it is possible to read off from the periods certain important information relating to the mirror manifolds.